Schools' Challenges in Distance Learning during Emergency Education: Focus Group Methodology - Wajeeh Daher (MDPI AG, 2024)
The present research uses the focus group discussion methodology to report the challenges met by the educational system in distance education during emergency education. It shows the different potentialities of this use. In doing this, it studies the practices used by schools during emergency education. Furthermore, the research verifies the suggestions given by a group of educationists to cope with challenges in emergency education. A focus group of nine participants met in the frame of a Ph.D. course to discuss the issues in which the present research is interested, and the number of discussion sessions was four. The research results indicated that the reasons varied for agreement and disagreement in the FGDs, where these reasons were mostly experience-based, perception-based, affiliation-based, inconsideration-based, compromise-based, and suggestion-based. Moreover, the types of agreement and disagreement were mostly complementary, vis-à-vis agreement-with-objection and agreement-with-advancement. The facilitator performed the following different functions: (1) initiator, (2) caring about the different voices in the FGD, and thus encouraging equity in the FGD, (3) making the discussion smooth, (4) advancing the discussion, (5) and orchestrating the discussion. In addition, the discussion of the participants addressed challenges related to the teachers, to the Ministry of Education, and to the resources. The schools' and the Ministry of Education's practices included different actions in an attempt to overcome the challenges of distance education: holding workshops related to distance education, suggesting the schools as places for the teachers to teach their online lessons, and making declarations for the public and families. The suggestions given by the participants to maintain and improve online learning included communicating with the students and holding workshops for the professional development of teachers at regular times. Close relationships between the Ministry of Education, the schools, and the parents were recommended in order to maintain an acceptable level of distance education.